Assessing engagement in people with dementia: A new approach to assessment using video analysis - Jones, C.; Sung, Billy; Moyle, W. (W.B. Saunders Co., 2015)
The study of engagement in people with dementia is important to determine the effectiveness of interventions that aim to promote meaningful activity. However, the assessment of engagement for people with dementia in relation to our current work that uses social robots is fraught with challenges. The Video Coding - Incorporating Observed Emotion (VC-IOE) protocol that focuses on six dimensions of engagement: emotional, verbal, visual, behavioral, collective and signs of agitation was therefore developed. This paper provides an overview of the concept of engagement in dementia and outlines the development of the VC-IOE to assess engagement in people with dementia when interacting with social robots.